Levels and determinants of malnutrition among India's urban poor women: An analysis of Demographic Health Surveys 2006 and 2016. Issue 3 (5th March 2020) - Sethi, Vani; de Wagt, Arjan; Bhanot, Arti; Singh, Konsam Dinachandra; Agarwal, Praween; Murira, Zivai; Bhatia, Salima; Baswal, Dinesh; Unisa, Sayeed; Subramanian, S. V.
Abstract: A quarter of 400 million urban Indian residents are poor. Urban poor women are as undernourished as or worse than rural women but urban averages mask this disparity. We present the spectrum of malnutrition and their determinants for more than 26, 000 urban women who gave birth within 5 years from the last two rounds of Demographic Health Survey 2006 and 2016. Among urban mothers in the lowest quartile by wealth index (urban poor), 12.8% (95% CI [11.3%, 14.5%]) were short or with height < 145 cm; 20.6% (95% CI [19%, 22.3%]) were thin or with body mass index < 18.5 kg/m 2 ; 57.4% (95% CI [55.5%, 59.3%]) had any anaemia (haemoglobin < 12 g/dL), whereas 32.4% (95% CI [30.5%, 34.3%]) had moderate to severe anaemia; and 21.1% (95% CI [19.3%, 23%]) were obese (body mass index ≥ 25 kg/m 2 ). Decadal gains were significant for thinness reduction (17p.p.) but obesity increased by 12 p.p. Belonging to a tribal household increased odds of thinness by 1.5 (95% CI [1.06, 2.18]) times among urban poor mothers compared with other socially vulnerable groups. Secondary education reduced odds of thinness (0.61; 95% CI [0.48, 0.77]) and higher education of short stature (0.41; 95% CI [0.18, 0.940]). Consuming milk/milk products, pulses/beans/eggs/meats, and dark green leafy vegetables daily reduced the odds of short stature (0.52; 95% CI [0.35, 0.78]) and thinness (0.72; 95% CI [0.54, 0.98]). Urban poor mothers should be screened for nutritional risks due to the high prevalence of all forms of malnutrition and counselled or treated as per risk.